The bicentennial in Colombia memory, patrimony and land - Castiblanco Roldán, Andrés F. (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This text presents a number of reflections related to the bicentennial and some implications about the memory and land as basic concepts which support the Colombian society through the patrimony. This theoretical implication ends in the resume of the dialogues between Santander and Bolivar, known as independence symbols, but also it is looking for those representations in their speeches that involve the memory of the home country.